Application of Information Technology to Criminal Information Cases - Chanhom, Kanaphon (Naresuan University Law Journal, 2015)
The study focuses on designing an effective type of information technology to criminal information cases in the process of prosecution. At present, some practical problems occur during the criminal information process. Bring information technology to the criminal information procedure can help the process more effective and fairer to parties. For doing this, the Code of Criminal Procedure the Criminal Act on Establishment of District Courts and Criminal Procedure in District Court B.E. 2499 and the Rules of the Office of the Attorney General need to be amended to serve the new information technology system.